Keanekaragaman Dan Kelimpahan Jenis Gastropoda Di Zona Intertidal Pantai Longot Desa Lewoblolong Kecamatan Ile Boleng Kabupaten Flores Timur Sebagai Media Pembelajaran Biologi - Boleng, Yuliana Anggy; Djalo, Aloysius; Ndukang, Sardina (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2024)
Longot Beach is one of the spiritual tourism destinations located in Lewoblolong Village, Ile Boleng District, East Flores Regency. To date, the number and types of gastropods in the intertidal zone of Longot Beach remain unknown. The purpose of this research is to determine the diversity and abundance of gastropod species at Longot Beach and to develop a biology learning medium in the form of a booklet. This research employs a research and development approach using the ADDIE model. The findings revealed 12 species of gastropods, namely Costoanachis sertulariarum, Cypraea pantherina, Conus miliaris, Conus lividus, Cypraea annulus, Nerita exuvia, Cellana nigrolineata, Cerithium zonatum, Cabestana cutacea, Canarium mutabile, Strombus alatus, and Nassarius mutabilis. The diversity index was calculated at 2.369803632, which falls into the moderate category. The highest species abundance index was 1.1 ind/m², while the lowest was 0.2 ind/m². The validation results of the booklet by media experts achieved a percentage of 80.08%, and by material experts, 89.28%, with an average of 84.68%, categorized as highly valid as a learning medium. The conclusion of this study is as follows: 12 species of gastropods were identified at Longot Beach with a diversity index in the moderate category, species abundance of 0.2 ind/m², and the developed booklet on gastropod diversity and abundance at Longot Beach in Lewoblolong Village is classified as valid for use as a learning medium.